Sistem Pencernaan pada Manusia - Anisya Candra Denvisintami; Gita Laili Maulida Syarifa; Kharisma Putri Cahya Ningrum; Lelyana Sekar Rahmaputri; Maisela Arya Rahmawati; Uswatun Khasanah; Liss Dyah Dewi Arini (INDO PUBLISHING, 2025)
The human digestive system is the process of converting food through the breakdown of food into simple particles aided by enzymes and the absorption of nutrients to meet the body's needs. The purpose of this journal is to understand respiration in the human digestive system. A literature review method was used. Data was collected from scientific articles on respiration and digestion published in books and journals. From this explanation, it can be concluded that the digestive system functions to provide the body with air, food, and electrolytes from digested nutrients so they can be absorbed. The digestive tract includes the mouth, throat (pharynx), esophagus, stomach, small intestine, large intestine, rectum, and anus. The digestive system also includes organs outside the digestive tract, namely the pancreas, liver, and bladder.